Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1016/j.ejvs.2008.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Serum Myoglobin and Renal Morbidity and Mortality following Thoracic and Thoraco-Abdominal Aortic Repair: Does Rhabdomyolysis Play a Role?

Abstract: A strong relationship between postoperative serum myoglobin and renal failure suggests a rhabdomyolysis-like contributing aetiology following thoraco-abdominal aortic repair. We postulate a novel mechanism of renal injury for which mitigation strategies should be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Thus, Miller et al demonstrated a “relationship between intraoperative leg ischemia and postoperative renal failure, providing epidemiological evidence that the ischemic leg may be an important contributor to rhabdomyolysis-like renal morbidity after thoracoabdominal aortic surgery” [15]. The importance of peripheral muscle ischemia-reperfusion and rhabdomyolysis as a significant factor in the renal alterations was also stressed in other studies [4, 31]. Tallgren et al noticed increased preoperative albuminuria and postoperative acute renal dysfunction in 22% of patients with a 4% incidence of postoperative renal failure [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, Miller et al demonstrated a “relationship between intraoperative leg ischemia and postoperative renal failure, providing epidemiological evidence that the ischemic leg may be an important contributor to rhabdomyolysis-like renal morbidity after thoracoabdominal aortic surgery” [15]. The importance of peripheral muscle ischemia-reperfusion and rhabdomyolysis as a significant factor in the renal alterations was also stressed in other studies [4, 31]. Tallgren et al noticed increased preoperative albuminuria and postoperative acute renal dysfunction in 22% of patients with a 4% incidence of postoperative renal failure [14].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, lower limb ischemia-reperfusion is well known to result in remote organ injuries, key factors increasing perioperative and long-term morbidities [48]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In non-traumatic patients after elective surgery RML usually occurs as a result of compression because of unsuitable positioning or tourniquet use, but there are other contributing factors that should be considered [4]. Recently it has been recognized that myoglobinemia-induced acute kidney injury (AKI) may play a crucial role in surgical settings, especially with urologic [5] and thoraco-abdominal aortic surgery [6]. In bariatric surgery, RML is considered a consequence of the high pressure on the muscles on the operating table [7].…”
Section: Introductionmentioning
confidence: 99%
“…Distal aortic perfusion for protection of the spinal cord requires cannulation of the femoral artery, with perfusion pressure and peri-cannula hemostasis maintained traditionally by securing the cannula into the artery with a tourniquet (Fig 1) In a previous publication, we reported that patients who experience loss of the local leg-channel somatosensory evoked potential (SSEP) distal to the cannulation site during surgery are at increased risk for postoperative renal dysfunction, compared to patients who do not demonstrate this sign of functional ischemia (7). We found in a further follow-up study that serum myoglobins are also markedly increased in patients who experience postoperative renal dysfunction (8). These two findings have provided strong enough circumstantial evidence of a role for rhabdomyolysis in the etiology of renal failure, that our team has gradually modified our perfusion technique to reduce ischemia to the leg downstream of the cannulation site by use of a sidearm graft (Fig 2).…”
Section: Introductionmentioning
confidence: 84%